Poly[(μ(3)-nicotinato-κO:O':N)(μ(2)-nicotinato-κO,O':N)iron(II)]. - Ng, S.W. (International Union of Crystallography, 2008)
In the crystal structure of the title compound, [Fe(C(6)H(4)NO(2))(2)](n), one nicotinate group O,O'-chelates one Fe atom and binds through the N atom to the other Fe atom; the second nicotinate group bridges three Fe atoms through the N and two O atoms. The μ(2)- and μ(3)-bridging modes of the two nicotinate groups result in a polymeric three-dimensional network structure. The Fe atom shows octa-hedral coordination geometry but one of the Fe-O bonds is somewhat long [2.522 (2) Å].